A parametric study on the final blade installation process for monopile wind turbines under rough environmental conditions. (1st October 2018) - Jiang, Zhiyu; Gao, Zhen; Ren, Zhengru; Li, Ye; Duan, Lei
Highlights: A single blade installation model with realistic parameters is considered for an offshore monopile wind turbine. The blade final installation stage is analyzed considering motions of the blade root, hub, guide pin, and flange hole. Effects of various environmental parameters on the alignment and mating processes are investigated. The approach presented in this paper can serve as a tool for planning of marine operations. Recommendations are made for assessment of the blade alignment and mating processes. Abstract: Single blade installation is a method for installing wind turbine blades. If a jack-up vessel is used during an o shore installation, the wind turbine blade is mainly subjected to wind loads and experiences resonant motions, and the monopile is subjected to wave-induced vibrations. The blade mating process can be challenging if large relative motions occur between the blade root and the monopile top. This study numerically models a blade installation system that consists of a pre-installed monopile and nacelle assembly, and a 5 MW blade with tugger lines. By analyzing the blade-root and the hub motion radii from time-domain simulations, we evaluate the effects of mean wind speed, wind turbulence, significant wave height, wave spectrum peak period, wind-wave misalignment, and water depth on the blade installation. For the alignment phase, the blade-root motion is critical, especially when the mean wind speed and turbulence are high. The hub motion can be important when the monopile resonant responses are prominent. The relative in-plane motions rather than the hub or the blade motion alone should be considered during the assessment. For the mating phase, the high-frequency components of the responses are important in general. Because of the dominant flange-hole motions at the monopile top, an increase in water depth reduces the success rate of mating.